Factors influencing financial statement disclosure: Empirical evidence from Indonesia - Eka Hariyani; Khoirul Aswar; Meilda Wiguna; Ermawati; Yuneita Anisma (Investment Management & Financial Innovations, 2022)
Identifying the characteristics of Indonesian local governments that disclose financial statements looks relevant in order to find out the reasons for local governments in making policies to disclose financial statements. This study aims to examine whether financial condition, financial independence and political competition have an effect on the disclosure of financial statements in local governments, particularly districts/cities in Sumatra, Indonesia. A sample of 151 districts and cities on the Indonesian island of Sumatra were used in this quantitative analysis. The use of cluster sampling due to the implementation of accrual accounting based on the government regulation No. 71 of 2010 is applied in all districts/cities in Sumatra and has the same characteristics. The data analysis technique used in this study is a multiple linear regression with the SPSS test tool. The results reveal that factors influencing the financial statements disclosure is influenced by financial conditions (β = 0.095; p < 0.05), financial independence (β = 0.069; p < 0.05), and political competition (β = 0.038; p < 0.05). Overall, the results show a strong conclusion regarding the factors that affect the financial statements of the Indonesian government. The findings of this investigation can be a useful consideration for local governments in improving the quality of their external communications and improving public governance.